Evaluation of effectiveness of (elements of) parenting support in daily practice of preventive youth health care; design of a naturalistic effect evaluation in 'CIKEO' (consortium integration knowledge promotion effectiveness of parenting interventions) - Dafna A. Windhorst; Yuan Fang; Irene N. Fierloos; Matty R. Crone; Krista Van Mourik; Harrie Jonkman; Clemens M. H. Hosman; Wilma Jansen; Hein Raat (BMC, 2019)
Abstract Background The number of interventions to support parents is growing. The level of evidence regarding these intervention varies. In this paper we describe a study that aims to assess the effectiveness of specific 'elements' within such parenting interventions for families with children up to 7 years. A naturalistic effect evaluation will be applied. Study questions are: 1.What is the exposure of parents to (elements of) parenting interventions in the daily practice of preventive youth health care?2.What are the associations between the exposure to (elements of) parenting interventions and outcomes in parents/children related to parenting and child development? Methods/design Thousand parents/caregivers are recruited by preventive youth health care providers in the Netherlands. Measurements will be performed after inclusion and after 12-months follow up. Data regarding child/parent/caregiver characteristics, use of (parenting) interventions and care, and outcomes with regard to parenting skills, family functioning and child development will be collected. Outcomes will be compared between parents/children exposed and non-exposed to the (elements of) parenting interventions (adjusting for confounders). Discussion We hypothesize that parents/caregivers with exposure to (elements of) parenting interventions show (relatively more) improvements in parenting outcomes. Results will support intervention selection/development, and support communities/professionals to select appropriate intervention-elements. Trial registration Netherlands National Trial Register number NL7342. Date of registration: 05-November-2018, retrospectively registered.